Corifollitropin alfa: a novel long-acting recombinant follicle-stimulating hormone agonist for controlled ovarian stimulation. (September 2010) - Loutradis, D; Vlismas, A; Drakakis, P
The advent of recombinant technology has made the production of modified proteins with desired properties possible. Corifollitropin alfa is a successful example of the first available long-acting, follicle stimulating hormone. Corifollitropin alfa has prolonged half-life and a slower absorption rate, but has the same receptor-binding and biological activity as recombinant FSH (rFSH). Its application is associated with the arrival of a novel simplified approach for controlled ovarian stimulation in IVF patients. Different studies have proven the efficiency of a single corifollitropin alfa dose to initiate and sustain multiple follicular development in a gonadotropin-releasing hormone antagonist protocol. Finally, corifollitropin alfa is well tolerated and is not correlated with serious adverse events, except for the slightly higher incidence of ovarian hyperstimulation syndrome compared with traditional management with recombinant FSH.